Time-Driven Activity-Based Costing in the Assembly Industry - Olga Vedernikova; Lorena Siguenza-Guzman; Johanna Pesantez; Rodrigo Arcentales-Carrion (Australasian Accounting, Business and Finance Journal, 2020)
Costs and their determination play a critical role in all manufacturing companies. The traditional costing system has received criticism resulting from the arbitrary allocation of indirect manufacturing costs. As an important initiative to address its weaknesses, new costing methods such as the Time-Driven Activity-Based Costing (TDABC) have emerged. Unfortunately, up to our knowledge, no investigations have been applied in analyzing assembly companies thoroughly nor considering all the processes necessary to obtain the final products. This article explores the TDABC application in the assembly industry through comparison with traditional volume-based costing by focusing on manual and semi-automatized production. Since the research is descriptive, a multiple-case study design was implemented in the assembly of televisions, motorcycles, and printed circuit boards. The developed methodology allowed determining the existence of factory overhead and direct labor cost variances between two different cost accounting systems, which also affected the unit cost of the products. Findings also highlight the benefits of TDABC application in the assembly industry, along with the shortcomings and future potential of research in this area.
Keywords: Assembly industry; Processes; Time-Driven Activity-Based Costing; TDABC